Effects of slime toy poisoning in children and teenagers - Maicon Jeferson Silva de Oliveira; Maria Vitória França Bezerra; Rodrigo Azevedo Loiola; Gabriela Souza de Lima; Gustavo Henrique Oliveira da Rocha; Rômulo Tadeu Dias de Oliveira; Éric Diego Barioni (Sociedade de Pediatria de São Paulo, 2022)
Abstract Objective: The aim of this study was to identify which types of skin reactions are associated with slime toys and which of their ingredients are most frequently involved in cases of poisoning. Data source: Between January and July 2021, articles were selected using PubMed, SciELO, and LILACS databases. The following descriptors were used: (dermatitis OR rash OR eczema OR inflammation) AND slime. Inclusion criteria were articles available in full, in either Portuguese, English, or Spanish, published between January 2000 and July 31, 2021, and articles reporting cases of contact dermatitis or eczema potentially or directly attributed to slime toys. Articles not meeting these criteria and duplicate texts in the databases were excluded. Data synthesis: In total, 65 publications were identified, of which 16 were included in this review. This resulted in a total of 22 children (2 males, 20 females), aged between 4 and 13 years, who were reportedly intoxicated by slime toys, most of these being linked to homemade preparations. Studies reported the occurrence of contact or allergic dermatitis on hands, fingers, nails, forearms, and cheeks. The most allergenic and/or irritant ingredients included liquid detergent and soap. Additionally, patch tests identified positive reactions to methylisothiazolinone and methylchloroisothiazolinone, the preservatives used by chemical industries on preparation of glue, soap, detergents, etc. Conclusions: Although slime toys might be important for improving motor development and parental relationships, homemade slime toy recipes include several allergenic and irritant ingredients which might be exposed to vulnerable children and cause intoxications. Therefore, homemade slime toys preparations should be used cautiously and under the supervision of adults.